ALAT UKUR KADAR EMISI DAN KEBISINGAN KNALPOT PADA KENDARAAN BERMOTOR - , ARYUN RIFQI BAIQUNI; , Ariesta Martiningtyas H., S.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
All vehicles and motorcycle in the city has a standard regulation in pollution aspect which ruled by the government and police department. There are a lot of motorcycles and vehicle types in the city but the concern here are the private vehicles and motorcycles. There are some problems In the private vehicles and motorcycles presence in the city like sound pollution which is effect of using unauthorized exhaust type and remaining unused gas pollution from the exhaust as the effect of unperfectly engine fuel burning process. Unfortunately, the police department and the government who make the regulation are not inspect gas pollution and sound pollution from vehicles and motorcycle carefuly. To inspect the sound pollution there is a need of tool which contain sound level meter and mic condenser. To inspect the gas pollution needs mq gas sensor. To measure sound pollution inspector should make a distance about 20-30cm between the tool and the exhaust. To measure gas pollution the aspect include of CO, HC, and Nox. Arduino Uno is used to control both of the system. The result accomplished from the project are builded a tool to examine the sound polution and exhaust gas emision based on Arduino Uno that could display the result of the measurement in unit of dB, ppm, and percent (%).